Caesarean section scar endometriosis: a case report and review of literature - Rathod, Setu; Samal, Sunil Kumar; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is described as the presence of functioning endometrial tissue outside the uterine cavity. Scar endometriosis is a rare event which usually develops after pelvic operations involving the uterus and fallopian tubes. The symptoms are nonspecific, typically involving abdominal wall pain at the incision site at the time of menstruation. Its diagnosis can sometimes be difficult and may be confused with various other surgical conditions. We present here a case of abdominal wall scar endometriosis in a woman who has undergone caesarean delivery three years prior to her current presentation. The epidemiology, pathogenesis, clinical features, diagnosis, treatment and methods of prevention of this somewhat rare condition are discussed.